Komunikasi Kebencanaan Berbasis Kearifan Lokal (Studi Kasus Banjir Bandang dan Longsor Aceh Tengah dan Bener Meriah) - Makmur Jaya (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
The flash floods and landslides that occurred in Central Aceh and Bener Meriah Regencies demonstrate that disaster issues are not only related to natural factors but are also influenced by community social communication patterns. This study aims to analyze disaster communication based on local wisdom to improve preparedness, emergency response, and recovery of disaster-affected communities. The study used a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with traditional leaders, religious leaders, village officials, and affected communities, as well as field observations and documentation studies. The results indicate that the local wisdom of the Gayo community, such as the role of the village reje, mosque imam, customary deliberations, and the value of maintaining natural balance, serves as an effective and trusted disaster communication medium. However, this local wisdom has not been optimally integrated into the formal disaster communication system of the local government. This study recommends strengthening the synergy between modern communication and local wisdom as a sustainable and contextual disaster communication strategy.